A multiple-time-step integration algorithm for particle-resolved simulation with physical collision time. (June 2023) - Zhu, Zhengping; Hu, Ruifeng; Zheng, Xiaojing
Abstract: In this paper, we present a multiple-time-step integration algorithm (MTSA) for particle collisions in particle-resolved simulations. Since the time step required for resolving a collision process is much smaller than that for a fluid flow, the computational cost of the traditional soft-sphere model by reducing the time step is quite high in particle-resolved simulations. In one state-of-the-art methodology, collision time is stretched to several times the flow solver time step for the fluid to adapt to the sudden change in particle motion. However, the stretched collision time is not physical, the hydrodynamic force may be severely underestimated during a stretched collision, and the simulation of sediment transport may be sensitive to the stretched collision time. The proposed MTSA adopts different time steps to resolve fluid flow, fluid–particle interaction, and particle collision. We assessed the MTSA for particle–wall collisions as well as particle–particle collisions, determined the optimal iteration number in the algorithm, and obtained excellent agreements with experimental measurements and reference simulations. The computational cost of the MTSA can be reduced to about one order of magnitude less than that using the traditional soft-sphere model with almost the same accuracy. The MTSA was then implemented in a particle-resolved simulation of sediment transport with thousands of particles. By comparing the results obtained using the MTSA and a version of the stretching collision time algorithm similar to Costa et al. (2015), we found that stretching the collision time reduced particle stiffness, weakened particle entrainment, and affected some turbulence and particle statistics. Highlights: A novel time integration algorithm for particle-resolved simulations with physical collision time is proposed. Three different time steps are designed for fluid flow, fluid–particle interactions and particle collisions, respectively. The algorithm can preserve the physical collision time, and reduce the computational cost by about one order of magnitude. The algorithm is applied to particle–wall and particle–particle collisions, as well as sediment transport cases.